Removal of heavy metals from wastewater using carbon nanotubes - Mujawar, Mubarak; Sahu, J.; Abdullah, E.; Jayakumar, N. (2014)
The discovery of carbon nanotubes (CNTs) and the prospect of developing novel carbon-based nanomaterials have attracted researchers worldwide. CNTs have great potential as a novel type of adsorbent due to their unique properties such as chemical stability, mechanical and thermal stability, and the high surface area, which leads to various applications including hydrogen storage, protein purification and water treatment. Removal of heavy metals from industrial wastewater leads to the biggest challenge nowadays. To reduce environmental problems, the CNTs are promising candidates for the adsorption of heavy metals. In this study, extremely brief summaries of liquid pollutant purification are reviewed.